'It doesn't happen … and I've never thought it was necessary for it to happen': Barriers to vulnerable defendants giving evidence by live link in Crown Court trials. (July 2017) - Fairclough, Samantha
Witnesses and defendants are able to give evidence by live link provided that they meet the vulnerability criteria set out in the Youth Justice and Criminal Evidence Act (1999). The vulnerability criteria include, in brief, the defendant or witness being young and/or suffering from a physical, mental or learning disability. Findings from interviews undertaken with 18 criminal practitioners indicate that, even when a defendant is sufficiently vulnerable to qualify for the use of live link, the provision is rarely invoked. Drawing on this data, this article identifies a series of barriers which contribute heavily to the inaccessibility of the live link provision to vulnerable defendants giving evidence in their trials.